2020
DOI: 10.7883/yoken.jjid.2019.304
|View full text |Cite
|
Sign up to set email alerts
|

Nonmetabolizable Arabinose Inhibits <i>Vibrio</i> <i>cholerae</i> Growth in M9 Medium with Gluconate as the Sole Carbon Source

Abstract: Marine bacterium Vibrio cholerae, belonging to serogroups O1 and O139 are responsible to cause cholera in human. Pentose sugar arabinose is nonmetabolizable by the pathogen and is present in environmental niches as well as in the human intestine. In this study, arabinose mediated V. cholerae growth interference has been assessed in M9 minimal medium containing gluconate as sole carbon source in the light of Entner-Doudoroff (ED) pathway, an obligatory metabolic route for gluconate utilization. V. cholerae O1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…It was recently reported that L-Ara inhibits the proliferation of V. cholerae [14]. Here, we show that it is associated with a change in the morphology of the cell from a curved rod shape to a spherical form (Figure 1).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It was recently reported that L-Ara inhibits the proliferation of V. cholerae [14]. Here, we show that it is associated with a change in the morphology of the cell from a curved rod shape to a spherical form (Figure 1).…”
Section: Discussionsupporting
confidence: 69%
“…Nevertheless, the E. coli PBAD system proved to be very effective in V. cholerae, which suggested that L-Ara was imported in the cytoplasm of the cells. However, we and others recently reported that L-Ara could interfere with the growth of the bacterium, calling for a better understanding of the impact of L-Ara on the physiology of V. cholerae and the pathway leading to its toxicity [14].…”
Section: Introductionmentioning
confidence: 97%
“…It was recently reported that L-Ara inhibited the proliferation of V. cholerae (15,16). Here, we show that it is associated with a change in the morphology of the cells from a curved rod shape to a spherical form (Figure 1).…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, the E. coli P BAD system proved to be very effective in V. cholerae, which suggested that L-Ara was imported in the cytoplasm of the cells. However, we and others recently reported that L-Ara could interfere with the growth of V. cholerae (15,16), calling for a better understanding of the impact of L-Ara on the physiology of this bacterium.…”
Section: Introductionmentioning
confidence: 93%